Accurate lymphadenectomy along the recurrent laryngeal nerve based on precise positioning during thoracoscopic–laparoscopic oesophagectomy: A retrospective cohort study. Issue 1 (February 2015) - Yang, Jianjun; Hong, Liu; Feng, Fan; Li, Mengbin; Sun, Li; Cai, Lei; Zhang, Hongwei
<x xml:space="preserve">Abstract</x> Aim Lymph nodes along the recurrent laryngeal nerves (RLN) are considered to be highly involved in oesophageal squamous cell carcinoma patients, and radical dissection of these lymph nodes is recommended. The present study aimed to demonstrate the value of thoracoscopic–laparoscopic oesophagectomy (TLE) in radical lymphadenectomy along the bilateral RLN. Patients and Methods From November 2010 to September 2012, 51 patients underwent TLE. The procedures during the radical lymphadenectomy along the bilateral RLN were done using ultrasonic scalpel with single‐lumen endotracheal tube intubation. Results The lymph nodes along the RLN could be sufficiently removed with an extremely low incidence of RLN injury. The mean number of lymph nodes removed was 3.58 ± 2.59 along the right RLN, and 2.73 ± 1.66 along the left RLN. There were two types of origin for right RLN; the origin of the majority was adjacent to the right subclavian artery, and the origin of three cases was away from the right subclavian artery. Conclusions TLE in combination with a single‐lumen tube, bilateral lung ventilation and semiprone position could be safely and efficiently applied in radical lymphadenectomy along the bilateral RLN. Ultrasonic scalpel could be safely used in lymphadenectomy along the RLN without increased heat injury of RLN.